Detection of cytokeratins in ghost cells of calcifying cystic odontogenic tumor indicates an altered keratinization and hair follicle differentiation for their development - Kaminagakura, Estela; Domingos, Patrícia Luciana Batista; da Rosa, Marize Raquel Diniz; Loyola, Adriano Mota; Cardoso, Sérgio Vitorino; Lopes, Maria Cândida de Almeida; Bonan, Paulo Rogério Ferreti; de Faria, Paulo Rogério (Elsevier, 2013)
Calcifying cystic odontogenic tumors (CCOTs) are benign cystic lesions of odontogenic origin characterized by an ameloblastoma-like epithelium and the presence of a group of cells named ghost cells. The pattern of cytokeratin (Ck) expression on these lesions remains unclear and needs to be clarified. To this end, the expression of Ck6, Ck13, Ck14, Ck18, and Ck19 in the epithelium lining of 7 cases of CCOTs was evaluated by immunohistochemistry. For this, the epithelium lining was divided into 3 distinct regions: basal layer, suprabasal layer, and the compartment composed of ghost cells. In this study, 6 cases (85.7%) were classified as type 1 and 1 (14.3%) as type 4. All cases were negative for Ck13 and Ck18, despite the epithelial layer, as well as in the ghost cells. Ck6 was only positive in the ghost cells. Positivity for Ck14 and Ck19 was found in the basal and suprabasal layers, including the ghost cells. The results showing positivity for Ck14 and Ck19 in all of the analyzed cases reinforce CCOT as being of odontogenic origin, and the restricted expression of Ck6 in the ghost cells may be indicative that these cells suffer an altered differentiation into hair follicles in CCOTs. © 2013 Elsevier Inc. All rights reserved.
Keywords: Calcifying cystic odontogenic tumor; Cytokeratins; Immunohistochemistry; Odontogenic; Pathogenesis; Tumors